Understanding early hydration in belite calcium sulfoaluminate cements: Impacts of minor elements and citric acid - Koufany, Imane; Fernández-Sánchez, Jaime; Cuesta, Ana; Santacruz-Cruz, María Isabel; Bescher, Eric P.; García-Aranda, Miguel Ángel; Gómez-de-la-Torre, María de los Ángeles (Elsevier, 2025)
This study investigates the early-age hydration behavior of eight belite calcium sulfoaluminate (BCSA) cement batches with nearly identical compositions and physical properties, yet exhibiting significantly different hydration kinetics. Two clusters were identified: relatively fast-setting cements with a final setting time of 22 min and a main calorimetric peak at 2 h, and relatively slow-setting cements with 28-minute setting times and peaks at 3 h. These values can be retarded by adding citric acid. The fast-setting cements displayed higher early concentrations of soluble potassium (149 mM) and sulfate (76 mM) than slow-setting cements (107 mM and 57 mM, respectively), attributed to greater potassium sulfate content. Higher alkaline content accelerates ye'elimite dissolution and hasten ettringite crystallization. Isothermal calorimetry and in-situ laboratory X-ray powder diffraction (analyzed via Rietveld refinement) confirmed that the differences in dissolution and crystallization kinetics underlie the observed variability. The addition of citric acid extended both initial and final setting times by approximately 1.8 h. Its retarding effect was most pronounced for anhydrite dissolution, with a smaller impact on ye'elimite dissolution and AFt crystallization. Pore solution analysis revealed that citric acid increased calcium and sulfate concentrations while reducing potassium levels, supporting a retardation mechanism involving calcium complexation and preferential sorption/deposition of citrate onto anhydrous phases. These findings underscore the importance of early-age phase-specific dissolution behavior in governing BCSA cement performance, particularly for applications requiring rapid setting and early strength development.
Keywords: Sulfatos; Calorimetría; Mecanismos de reacción (Química); Rayos X - Difracción; Rietveld, Método de